Menuju Keterlibatan Etis - Nathania, Leora; Kuddeh, Sabrina; Yuan, Nathania Delicia; Laelani, Nesia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research discusses the importance of ethical engagement in international relations in the current era of globalization. Ethical engagement demands responsibility from nations, international organizations, multinational corporations, and civil society to address issues such as human rights, social justice, environmental sustainability, and economic cooperation. Ethical principles such as justice, truth, and sustainability should form the basis of foreign policies and diplomatic actions to achieve global peace and prosperity. Despite challenges such as conflicting values and interests, implementing ethical engagement also presents opportunities to build fair and sustainable global relationships. The study utilized a qualitative approach with literature review analysis as the main method to gather and analyze data. Relevant literature was selected from academic databases and reliable sources discussing organizational culture, ethical behavior, and the implementation of ethical values in organizational contexts. Data were collected through in-depth analysis of articles, books, and other relevant documents. The findings indicate that ethical engagement in international relations is grounded in communication ethics and moral principles such as honesty, transparency, justice, and non-intervention. Humanitarian interventions respecting national sovereignty tend to be more successful. Multilateral diplomacy in the UN applies principles of equality and mutual respect to achieve fair and stable global solutions. In conclusion, communication ethics in international relations set accepted standards of behavior and build trust between nations. Moral principles provide the foundation for fair decision-making in humanitarian interventions and international actions. Human rights and environmental sustainability are also crucial for maintaining security within a country. These principles and ethics are essential for the effectiveness and security of a nation.